Just Peacemaking as Hermeneutical Key: The Need for International Cooperation in Preventing Terrorism - Stassen, Glen Harold (Journal of the Society of Christian Ethics, 2004)
DATA SHOW THAT THE STRATEGY OF ARGUING THAT A WAR IS UNJUST, or that we should oppose all wars, always loses the national debate that occurs before a war. Data also show, however, that articulating an alternative to the war fares much better. Facing this reality requires us to develop an additional ethic besides just war and pacifism—an ethic that articulates specific alternatives to a war.